Synthesized spatiotemporal mode-locking and photonic flywheel in multimode mesoresonators - Mingming Nie; Kunpeng Jia; Yijun Xie; Shining Zhu; Zhenda Xie; Shu-Wei Huang (Nature Communications, 2022)
Here the authors demonstrate spatiotemporal mode-locked dissipative Kerr soliton and enhanced photonic flywheel performances in both the fundamental comb linewidth and DKS timing jitter.